Arabic belles lettres - Lowry, Joseph E.; Toorawa, Shawkat M. 1963- (Resources in Arabic and Islamic studies, 2019)
Reading the Qur"an as a law book: Legislation, language and allusion in Islam's scripture / Lowry -- Matrilineal lineages as a signifier of social links in the context of Badr and Uhud / Abed el-Rahman Tayyara -- Rhapsody, revelation and the coming of the beloved: : Majnun Layl and the 'udhri romances / Ruqayya Y. Khan -- The rational, irrational, and recognition: Fir Sah, detection and the uncanny atavism of kinship in some medieval Arabic narratives / Philip F. Kennedy -- Medieval authors -- ʿUbayd Allah ibn Ahmad Ibn Abi Tahur and his (continuation of his father's) history of Baghdad / Shawkat M. Toorawa -- Ibn Faris and the origins of the Maqamah revisited / Maurice A. Pomerantz and Bilal W. Orfali -- The philosopher as littéerateur: Al-Tawhidi and his predecessors / Everett K. Rowson -- Championing the era: approaching Al-Khafaji's Rayhanat Al-Libba' / Ghayde Ghraowi -- Modern Egypt -- Cairene Newspapers and cultural controversy: a case from 1902 / Roger Allen -- "We're the ones who made the ants stand in line": preposterous boasts and the ideology of ingenuity in Egyptian Arabic / Devin J. Stewart -- Principal works of Everett K. Rowson, 1979-2018* -- Contributors -- Index of Names and Titles.